Isolasi Bakteri Pencemar pada Jajanan Tradisional di Kawasan Jalan Al-Falah - Ardepy, Sri; Sartini, Sartini; Rahmiati, Rahmiati; Siregar, Rahma Sari (Universitas Medan Area, 2024)
Traditional snack cakes can be contaminated with harmful microbes due to poor hygiene and sanitation practices. This study aims to identify the types of bacteria contaminating traditional snacks sold by street vendors on Jl. Al-Falah. The method used is the pour plate technique on Plate Count Agar for 24 hours at a temperature of 33-35 °C, along with selective media Salmonella Shigella Agar and Eosin Methylene Blue Agar. Observations include both fresh samples and those stored for 24 hours. Confirmation tests were conducted on SSA and EMBA media, followed by SCA (Simmon Citrate Agar). The results showed that six types of cakes exceeded the microbial contamination limits: P1S1 (6.2 × 10⁵ colonies/g), P2S1 (10 × 10⁴ colonies/g), P3S1 (4.8 × 10⁴ colonies/g), P1S5 (5.6 × 10⁴ colonies/g), P2S5 (5 × 10⁴ colonies/g), and P3S5 (8.6 × 10⁴ colonies/g). Out of 15 samples, two were detected to contain pathogenic bacteria: P1S1 was positive for Salmonella sp. and Escherichia coli, while P3S2 was positive for Escherichia coli. In conclusion, the contaminating bacteria Salmonella sp. and Escherichia coli were found in cake samples from different vendors.